2015
DOI: 10.1007/s00775-015-1318-7
|View full text |Cite
|
Sign up to set email alerts
|

Promising bifunctional chelators for copper 64-PET imaging: practical 64Cu radiolabeling and high in vitro and in vivo complex stability

Abstract: Positron emission tomography (PET) using copper-64 is a sensitive and non-invasive imaging technique for diagnosis and staging of cancer. A bifunctional chelator that can present rapid radiolabeling kinetics and high complex stability with 64Cu is a critical component for targeted PET imaging. Bifunctional chelates 3p-C-NE3TA, 3p-C-NOTA, and 3p-C-DE4TA were evaluated for complexation kinetics and stability with 64Cu in vitro and in vivo. Hexadentate 3p-C-NOTA and heptadentate 3p-C-NE3TA possess a smaller TACN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Using the same (or less) amount of sEVs (~ 106 nm) as Banerjee and his group, they achieved considerably higher RLY (91.2 ± 0.2% vs. ~ 20%). This could be the result of the well-known high radiochemical stability of [ 64 Cu]Cu-NOTA complexes 109 , 110 . PEGylation had the desired effect of increased sEV circulation, decreased liver uptake and increased tumour uptake, particularly after 24 h (Fig.…”
Section: Radiolabelling Of Evs Using Pet Radionuclidesmentioning
confidence: 99%
“…Using the same (or less) amount of sEVs (~ 106 nm) as Banerjee and his group, they achieved considerably higher RLY (91.2 ± 0.2% vs. ~ 20%). This could be the result of the well-known high radiochemical stability of [ 64 Cu]Cu-NOTA complexes 109 , 110 . PEGylation had the desired effect of increased sEV circulation, decreased liver uptake and increased tumour uptake, particularly after 24 h (Fig.…”
Section: Radiolabelling Of Evs Using Pet Radionuclidesmentioning
confidence: 99%
“…It is well-known that the radiometal chelators could have significant effect on probe distribution in vivo. [34][35][36] Therefore, in this report, 3 radiometal chelators are conjugated to NT peptides (DOTA-NT, NOTA-NT, and AmBaSar-NT) aiming to select the most potent one for in vivo imaging applications. After conjugation, cell binding assay confirmed that addition of the chelate on the C-terminal lysine has minimal effect on NTR binding capacity.…”
mentioning
confidence: 99%
“…NOTA and derivatives are well-known to form a very stable complexes with 68 Ga and with 64 Cu [ 100 , 101 ]. Coordination of 68 Ga with DOTA derivatives is less efficient, often requiring heating (80–100°C).…”
Section: Spacers Chelators and Radionuclidesmentioning
confidence: 99%